ANALISIS ALIRAN AIR TANAH SATU DIMENSI (KAJIAN LABORATORIUM) - SAROHA SIMAREMARE (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2015)
In actual field case, research about ground water flow is difficult to carry aout, for this reason ground water head and characteristics is studied through ground water hydraulic model at laboratory. The research conducted was about ground water hydraulic modeling at Laboratory by using Ground Water Flow Apparatus. Two Sand samples were used . The hydraulic head was measured and compared with calculated one. The result showed that average absolute error was 0.0014 for model I, 0.003 for model II, 0,005 for model III on 1st soil sample and 0,0010 for model I, 0,0008 for model II and 0,0003 for modekl III. The hydraulic conductivity was tested by using Constant Head Permeameter resulted in hydraulic conductivity 0,0052 cm/second for sample 1, 0,001723 m/second and 0,001723 cm/second for sample 2. Keywords : ground water, hydraulic conductivity, absolute error.